Tvorba 3D modelu kostela v Unkovicích - Pospíšilová, Iveta (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce je zaměřena na tvorbu 3D modelu kostela Nanebevzetí Panny Marie v Unkovicích. Předpokládá se, že výsledný digitální model bude v budoucnu využit k prezentaci budovy kostela. 3D model je zpracován na základě tachymetricky zaměřených bodů v programu Autodesk Inventor. Testováním přesnosti dle ČSN 01 3410 bylo prokázáno, že výsledný 3D model splňuje kritéria 3. třídy přesnosti.

My diploma thesis is focused on 3D model creation of a church of the Assumption of the Virgin Mary in Unkovice. The resulting digital model is supposed to be used for the church building presentation. 3D model is created on the basis of tacheometrically measured points in Autodesk Inventor. Accuracy testing according to ČSN 01 3410 proved confirmed criteria of 3rd accuracy rating.
Creation of 3D model of church in Unkovice
Keywords: Kostel; 3D model; Autodesk Inventor; Trimble SketchUp; Unkovice; Church; 3D model; Autodesk Inventor; Trimble SketchUp; Unkovice